2016
DOI: 10.1039/c6tb02078j
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic superoxide dismutase activity of MnO nanoparticles enhances the magnetic resonance imaging contrast

Abstract: MnO nanoparticles decompose superoxide and hydrogen peroxide in an enzyme-like manner leading to enhanced MRI contrast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…The development of nanocatalytic medicine has facilitated the emergence of various catalytic agents for enhancing MR contrast, by initiating in situ catalytic reactions and triggering paramagnetism elevation without toxic ions leakage, thus achieving simultaneously enhanced diagnostic efficacy, widened time windows, reduced administration dosage, and mitigated side effect. Ragg et al first demonstrated that MnO nanoparticles with dual enzyme‐like activities could act as efficient MR contrast agents in cancer diagnosis ( Figure ) . The SOD‐like activity of MnO nanoparticles enables catalytic decomposition of intratumoral O 2 •− into H 2 O 2 , as illustrated in the following equations: normalO2+Mn2++2normalH+normalHnormal2normalO2+Mn3+ normalO2+Mn3+normalO2+Mn2+…”
Section: Nanocatalytic Medicine For Diagnostic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of nanocatalytic medicine has facilitated the emergence of various catalytic agents for enhancing MR contrast, by initiating in situ catalytic reactions and triggering paramagnetism elevation without toxic ions leakage, thus achieving simultaneously enhanced diagnostic efficacy, widened time windows, reduced administration dosage, and mitigated side effect. Ragg et al first demonstrated that MnO nanoparticles with dual enzyme‐like activities could act as efficient MR contrast agents in cancer diagnosis ( Figure ) . The SOD‐like activity of MnO nanoparticles enables catalytic decomposition of intratumoral O 2 •− into H 2 O 2 , as illustrated in the following equations: normalO2+Mn2++2normalH+normalHnormal2normalO2+Mn3+ normalO2+Mn3+normalO2+Mn2+…”
Section: Nanocatalytic Medicine For Diagnostic Applicationsmentioning
confidence: 99%
“…e) T 1 ‐ (left) and T 2 ‐weighted MR images of MnO solutions. a–e) Reproduced with permission . Copyright 2016, Royal Society of Chemistry.…”
Section: Nanocatalytic Medicine For Diagnostic Applicationsmentioning
confidence: 99%
“…By analyzing the corresponding fluorescence intensity, the distribution of glucose in cancer cells could be mapped. [30c] The MnO‐based nanosystem with selective response toward superoxide radicals is capable of enhancing the magnetic resonance (MR) imaging contrast by sequential catalytic reaction . Based on the catalase‐like activity of MnO 2 toward H 2 O 2 , the in situ oxygen generation and upconversion luminescent imaging can be achieved simultaneously, which is capable of achieving the desirable cancer theranostics via the oxygen‐elevated synergetic radio/photodynamic therapy (PDT) .…”
Section: Applications Of Nanozymesmentioning
confidence: 99%
“…Nanozymes have increasingly attracted significant interest since we first uncovered the intrinsic peroxidase‐like activity of Fe 3 O 4 nanoparticles (NPs) in 2007. [ 3 ] Up to now, there are hundreds of nanomaterials that have been found to mimic the catalytic activity of peroxidases, [ 4,5 ] oxidase, [ 6 ] catalase, [ 7 ] haloperoxidase, [ 8,9 ] monooxygenase, [ 10 ] hydrolase, [ 11,12 ] superoxide dismutase, [ 13,14 ] or multienzyme systems. [ 15,16 ] Along with the rapid development and deepening understanding of nanoscience and nanotechnology, nanozymes hold promise to serve as direct surrogates of traditional enzymes.…”
Section: Introductionmentioning
confidence: 99%